MENINGKATKAN KEMAMPUAN MENGENAL ANGKA 1-10 MELALUI PERMAINAN ARSITEK MENARA BAGI ANAK TUNAGRAHITA RINGAN - Nida Ria (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstrack: This research was conducted based on the problem found at SLB Negeri 1 Padang in which a student with mild mental retardation got difficulties to recognize numbers from 1 to 10. This problem was revealed based on the result of observation and assessment done by the researcher on the student’s development. This problem had hampered the student from learning mathematics and led him to an obstacle in daily life especially those related to numbers. Therefore, the researcher offered a solution by applying tower architect game. This research was designed for revealing whether the use of the game could improve the ability of student with mild mental retardation to recognize number from 1 to 10. This was an experimental research which used single subject design and A-B design. The data obtained in this research was analyzed by using visual analysis of graphic. The subject of the research was the student with mild mental retardation named X. The student’s ability to mention 1 to 10 in the baseline condition (A) was stable from the sixth to the tenth day. In the intervention condition, 10 meetings were held and the highest ability of the student in this session was 10. Based on the result of data analysis, it was figured out that the mean level in the baseline condition (A) was 6,7, meanwhile the mean level in the intervention condition (B) was 11. Further, the tendency of way in the baseline and intervention conditions improved. The percentage of the data overlapped was 10% indicating that the use of tower architect game in the intervention condition gave better influence on the student’s ability to recognize numbers from 1 to 10. After the intervention given, the student was able to mention number from 1 to 10 correctly. Hence, the use of tower architect game could improve the student with mild mental retardation ability to recognize number from 1 to 10 at SLB N 1 Padang. It was recommended to the teachers to apply tower architect game in the learning process of Mathematics for students with mild mental retardation. Kata kunci: Permainan Arsitek Menara ;  Kemampuan Mengenal Angka 1-10 ; Tunagrahita Ringan.